1999
DOI: 10.1177/0092070399274006
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Accurate Usage of Nutrition Facts Panel Information for Food Product Evaluations and Purchase Intentions

Abstract: The nutrition facts panel on food packages was designed to provide comprehensible quantitative nutrition information that would allow consumers to make more informed food choices that could result in significant long-term health benefits. This study (1) examines how accurately consumers can use nutrient information in the facts panel to determine if a product has more or less than the recommended daily values of certain nutrients and (2) offers predictions and tests of the relationships between this usage abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 19 publications
5
92
0
2
Order By: Relevance
“…Post-NLEA research has also focused on evaluating how consumers use nutritional information and the NLEA labeling format (Burton, Garretson, and Velliquette 1999). Moorman (1996) finds that the Nutrition Facts panel increases consumers' acquisition and comprehension of nutritional information.…”
Section: Brief Overview Of Food-labeling Regulationmentioning
confidence: 99%
“…Post-NLEA research has also focused on evaluating how consumers use nutritional information and the NLEA labeling format (Burton, Garretson, and Velliquette 1999). Moorman (1996) finds that the Nutrition Facts panel increases consumers' acquisition and comprehension of nutritional information.…”
Section: Brief Overview Of Food-labeling Regulationmentioning
confidence: 99%
“…The results suggest that the proposed Nutrition Facts Janiszewski, 2012). Although the NLEA has increased the salience to consumers of some 60 nutrients, such as fat and calories (Burton, Garretson, & Velliquette, 1999;Moorman, 1996), it 61 has not clearly led consumers to make healthier food choices (Balasubramanian & Cole, 2002; 62 Campos, Doxey, & Hammond, 2011; Petruccelli, 1996). Thus, various constituents have called 63 for changes to the Nutrition Facts label, noting that an update is needed to better reflect current 64 nutrition science and to help people gauge their actual nutrient intake ("FDA Proposes Updates M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 update serving sizes to better reflect how much of a product people typically consume in one 72 sitting today.…”
mentioning
confidence: 99%
“…Nonetheless, many adults, especially those that are older, want and need labels to be easier to understand (Burton and Andrews 1996;Kristal et al 1998). This study also suggests that consumers are proficient in using labels and that more accurate use of the nutrition information on the facts panel moderates the effect of product nutrition value on consumer evaluations (Burton et al 1999). Furthermore, a recent study by Kozup et al (2006) found that, when consumers are exposed to education efforts, they are more aware of the risk of disease related to the consumption of trans fat as presented on the nutrition facts panel.…”
Section: Methodsmentioning
confidence: 66%